Mathematics anxiety phenomenon among students: A study on five selected programs in UiTM Melaka / Mohd Hafiz Bin Mohammad Hamzah and Yusarima Binti Muhamad - Mohammad Hamzah, Mohd Hafiz; Muhamad, Yusarima (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2012)
Mathematics anxiety is a learned emotional response to one or more of the following: participating in Mathematics class, listening to a lecture, working through a Mathematics problem, or discussing Mathematics (Rossnan, S, 2006). Mathematics is a subject that involves multi-tasking tasks such as computational skills, problem solving and critical thinking (Sahin & Ahmet, 2010). Doing a multi-tasking works at a same time sometimes looks quite difficult for certain people.